Development of A Servant Leadership Model Based on Character Education Values to Improve the Quality of Learning of Educational Institutions - Pattipeilohy, Poltjes; Syunu Trihantoyo; Amrozi Khamidi; Nunuk Hariyati; Kaniati Amalia; Ayu Wulandari; Jems Sopacua; Oryza Hafshah Syafira (Jawda: Journal of Islamic Education Management, 2025)
The purpose of this research is to develop a servant leadership model based on character education values ​​to improve the quality of learning in educational institutions. This research is based on the need to advance education that focuses not only on cognitive aspects but also on student character development and staff professionalism. The method used was Research and Development (R&D), adapting the Borg & Gall model. The research was conducted at SMK PIKA Semarang for one semester, from January 2 to May 30, 2025. Informants in this study consisted of the principal, vice principal, teachers, school committee members, students, and administrative staff. The model was tested through a feasibility test (feasibility), a limited trial, and a large-scale trial involving 25 teachers and students. The results of the study indicate that the developed Servant Character Leadership (SCL) Model is theoretically feasible and practically effective in improving educational standards. The results of the model trial showed an overall increase in the effectiveness of school service leadership of 15.75% after the SCL model was implemented, as evidenced by improvements in indicators such as student engagement, learning outcomes, and teacher motivation. This model was also deemed highly practical, with an average practicality percentage of 89.33%. The SCL model's primary contribution is providing a holistic framework that integrates a service philosophy with character values ​​(such as religiousness, nationalism, independence, mutual cooperation, and integrity), thus contributing significantly to creating a work ethic focused on character development within the educational environment.